Author Correction: Individual variations in cardiovascular-disease-related protein levels are driven by genetics and gut microbiome. (December 2018) - Zhernakova, Daria; Le, Trang; Kurilshikov, Alexander; Atanasovska, Biljana; Bonder, Marc; Sanna, Serena; Claringbould, Annique; Võsa, Urmo; Deelen, Patrick; Franke, Lude; de Boer, Rudolf; Kuipers, Folkert; et al.
In the version of this paper originally published, there was a typographical error. In the Discussion, the sentence "In line with this, Ep-CAM-deficient mice exhibited increased intestinal permeability and decreased ion transport60, which may contribute to CVD susceptibility risk59 " originally read iron instead of ion transport. This error has been corrected in the HTML, PDF and print versions of the article.